Paris ebook The memoir. - Hilton, Paris (2023)
***An Instant New York Times Bestseller*** From the woman who is credited for launching what we know as the celebrity focused, "brand" driven, social media obsessed popular culture of today, comes an honest and surprising memoir that reckons with that truth, and shows that there is so much more to Paris Hilton than you might believe. This extended edition includes a bonus chapter detailing her motherhood journey. I was born in New York City on February 17, 1981, three days after Valentine's Day. From the time I was a toddler, my brain skipped and flickered with the chemical imbalance of ADHD. Sometimes it was too much. I'm not bragging or complaining about it, just telling you: This is my brain. It has a lot to do with how this whole book thing is going to play out, because I love run-on sentences—and dashes. And sentence fragments. I'm probably going to jump around a lot while I tell the story. I came of age during the most turbulent pop culture period ever. The character I played—part Lucy, part Marilyn—was my steel-plated armor. People loved her. Or they loved to hate her, which was just as marketable. I leaned into that character, my ticket to financial freedom and a safe place to hide. I made sure I never had a quiet moment to figure out who I was without her. I was afraid of that moment because I didn't know what I'd find. I wrote this book in an effort to understand my place in a watershed moment: the technology renaissance, the age of influencers. I also wrote this book so that the world could know who I am today. I focused on key aspects of my life that led to what I am most proud of—how my power was taken away from me and how I took it back, how I built a thriving business, a marriage and a family. There are so many young women who need to hear this story. I don't want them to learn from my mistakes; I want them to stop hating themselves for their own mistakes. I want them to laugh and cry and embrace every aspect of who they are with fearlessness and pride. We all have our own brand of intelligence, and, girl, fuck fitting in.